DESIGN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN PANCASILA KELAS VI SD NEGERI TAMBAKREJO 01 - Iffana FR; Ida Dwijayanti; Erma Khristiyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learner-centered learning is necessary for an independent curriculum. Using differentiated learning design is one way to build learner-centered learning. Since each student is different in terms of learning style, learning speed, interest, and skills, differentiated learning design can consider the individuality of each student with the aim to improve learning outcomes. This study was conducted to determine the comparison of learning outcomes with Teaching at the Right Level (TaRL), Culturally Responsive Teaching (CRT), and differentiated learning styles in learning Pancasila education. An integrated mixed method was used to collect skinative and quantitative data simultaneously, but analyzed separately and then combined to provide a more in-depth analysis. The results show that there is a significant improvement when learning action III using the learning style differentiation approach with a percentage of completeness of 82%.